2009
DOI: 10.1590/s1415-47572009005000074
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of genes associated with mastitis in dairy cattle

Abstract: In order to characterize the expression of genes associated with immune response mechanisms to mastitis, we quantified the relative expression of the IL-2, IL-4, IL-6, IL-8, IL-10, IFN-g and TNF-a genes in milk cells of healthy cows and cows with clinical mastitis. Total RNA was extracted from milk cells of six Black and White Holstein (BW) cows and six Gyr cows, including three animals with and three without mastitis per breed. Gene expression was analyzed by real-time PCR. IL-10 gene expression was higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 22 publications
(20 reference statements)
2
25
0
5
Order By: Relevance
“…Nevertheless, despite this breed's importance to the dairy industry, few studies have been published identifying genes capable of conferring resistance to mastitis in animals other than taurine breeds (Bos taurus taurus). There are indications of the existence of differences in the response profile to clinical mastitis among Gyr, Holstein and cross-bred animals (Fonseca et al, 2009(Fonseca et al, , 2011. Besides this, one of the main results of The Bovine HapMap Consortium (2009) was confirmation that cattle are divided into three main groups: European, Indian and African.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite this breed's importance to the dairy industry, few studies have been published identifying genes capable of conferring resistance to mastitis in animals other than taurine breeds (Bos taurus taurus). There are indications of the existence of differences in the response profile to clinical mastitis among Gyr, Holstein and cross-bred animals (Fonseca et al, 2009(Fonseca et al, , 2011. Besides this, one of the main results of The Bovine HapMap Consortium (2009) was confirmation that cattle are divided into three main groups: European, Indian and African.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that TNF-α and IL-8 are present in the milk from udders infected by Gram-negative bacteria, such as Escherichia coli, Klebsiella pneumoniae or Pseudomonas aeruginosa, but they are present in lower concentrations or not detected in the milk from cows with mammary glands infected by Staphylococcus aureus (Shuster et al, 1997;Riollet et al, 2000;Bannerman et al, 2004aBannerman et al, ,b, 2005. Another study by our group with commercial cattle with and without mastitis caused by natural infection showed a difference in the expression profile of the IFN-γ, IL-2 and IL-10 genes among animals of the Holstein BW and Gyr breeds (Fonseca et al, 2009).…”
Section: Discussionmentioning
confidence: 78%
“…The majority of studies have examined European breeds with artificially induced infection. Like this study, that by Fonseca et al (2009) also evaluated the expression of some genes in naturally infected cows, but of separate Holstein BW and Gyr breeds rather than crossbreed animals. In that study, the IL-6, IL-8 and TNF-α genes also failed to show significantly different expression between cows with and without clinical mastitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A resposta à resistência à mastite é uma característica complexa e os genes envolvidos na resposta imune têm sido indicados como fortes candidatos para determinar a resistência de animais (Ferens et al, 1998;Alluwaimi et al, 2003;Rambeaud et al, 2003;Oviedo-Boyso et al, 2007;Fonseca et al, 2009). O sistema imunológico é um mecanismo específico que um animal tem para limitar infecções, sendo fundamental para a sobrevivência do animal e, por isso, precisa atuar de forma eficiente.…”
Section: Introductionunclassified